THE EFFECT OF DIFFERENT IRRIGANTS WITH OR WITHOUT ULTRASONIC ACTIVATION ON ROOT DENTIN MICROHARDNESS - Irina Tsenova-Ilieva; Emilia Karova (Peytchinski Publishing, 2021)
Purpose: The aim of this in vitro study was to evaluate the effect of different irrigation regimens of root dentin microhardness. Materials and methods: Twenty extracted, single-rooted, non-endodontically treated upper incisors were decoronated and further sectioned longitudinally in buccolingual direction. The surfaces of all forty samples were polished, evenly distributed into four groups (n=10) and then immersed in the following solutions: group 1: 2% sodium hypochlorite for 2 minutes followed by 17% EDTA for 2 minutes; group 2: 2% sodium hypochlorite for 2 minutes followed by 17% EDTA for 2 minutes, both ultrasonically activated; group 3: 5.25% sodium hypochlorite for 2 minutes followed by 17% EDTA for 2 minutes; group 4: distilled water (control group). Afterwards, the samples were dried and subjected to microhardness testing by using 300g load with a dwell time of 20 seconds. The averaged values of each sample's Vicker's hardness numbers were calculated and statistically analyzed. Results: All irrigation regimens significantly decreased the mean hardness of dentin when compared to the control group 4 (p<0.05). Pair-wise comparison between the values of Group 1, Group 2, Group 3 resulted in no statistical significance (p>0.05) regardless of the concentration and the ultrasonic activation of the solutions. Conclusions: The dentin microhardness was decreased regardless of the irrigation protocols used. Additional studies should clarify the clinical relevance of the compromised mechanical properties of dentin tissue and their relationship with the overall treatment success.